Biomolecules Turn Self-Assembling Amphiphilic Block Co-polymer Platforms Into Biomimetic Interfaces - Yorulmaz Avsar, Saziye; Kyropoulou, Myrto; Di Leone, Stefano; Schoenenberger, Cora-Ann; Meier, Wolfgang P.; Palivan, Cornelia G. (Frontiers in Chemistry, 2019)
Biological membranes constitute an interface between cells and their surroundings and form distinct compartments within the cell. They also host a variety of biomolecules that carry out vital functions including selective transport, signal transduction and cell-cell communication. Due to the vast complexity and versatility of the different membranes, there is a critical need for simplified and specific model membrane platforms to explore the behaviors of individual biomolecules while preserving their intrinsic function. Information obtained from model membrane platforms should make invaluable contributions to current and emerging technologies in biotechnology, nanotechnology and medicine. Amphiphilic block co-polymers are ideal building blocks to create model membrane platforms with enhanced stability and robustness. They form various supramolecular assemblies, ranging from three-dimensional structures (e.g., micelles, nanoparticles, or vesicles) in aqueous solution to planar polymer membranes on solid supports (e.g., polymer cushioned/tethered membranes,) and membrane-like polymer brushes. Furthermore, polymer micelles and polymersomes can also be immobilized on solid supports to take advantage of a wide range of surface sensitive analytical tools. In this review article, we focus on self-assembled amphiphilic block copolymer platforms that are hosting biomolecules. We present different strategies for harnessing polymer platforms with biomolecules either by integrating proteins or peptides into assemblies or by attaching proteins or DNA to their surface. We will discuss how to obtain synthetic structures on solid supports and their characterization using different surface sensitive analytical tools. Finally, we highlight present and future perspectives of polymer micelles and polymersomes for biomedical applications and those of solid-supported polymer membranes for biosensing.